A case study of a phosphorus chemical firm's application of resource efficiency and eco-efficiency in industrial metabolism under circular economy. (15th January 2015) - Ma, Shujie; Hu, Shanying; Chen, Dingjiang; Zhu, Bing
Abstract: Circular economy plays an essential and useful role in China in considering economic and ecological sustainability. Individual firms, as the primary implements of a circular economy, are facing many obstacles at present in aspects of resource and ecological efficiency. Therefore, this study presents a set of tools to help decision makers better solve these problems and to guide resource-based chemical industries in sustainable development. First, this study describes resource efficiency based on the SFA of a selected P-chemistry firm and identifies the key potential opportunities for improvement using analysis tools and assessment tools. Furthermore, by applying eco-design and decision tools, a firm-level, P-chemical, circular economic system is designed and constructed. A phosphorus chemical optimization model is established, and relevant successive scenarios are generated. Finally, the corresponding feasible solutions and policy recommendations are proposed to improve economic benefit, resource efficiency, waste recycling rate, and eco-efficiency. After industry design, planning, and technological progress, the total economic benefit increases dramatically, and the recycling efficiencies of accompanying resources (F, Si, I, and S) improve by different degrees. The results demonstrate that the economic benefit of phosphorus products increases by 28.5%, and P utilization efficiency correspondingly increases from 81.1% to 94.7%. The comprehensive utilization efficiency of phosphor gypsum increases to 100%, and the eco-efficiency could be improved significantly by eliminating the phosphor gypsum stack. This study demonstrates that technological progress in mineral processing and the production of associated products is the endogenic motivation to increase economic benefit and improve resource efficiency. The method proposed in this paper can be applied, duplicated, and spread not only within the P-chemical industry but also in other resource-based chemical industries. Highlights: We provide decision makers with a toolbox to achieve sustainable development at the firm level. We introduce a systematic evaluation approach for resource-oriented firm performance. Economic, resource efficiency and eco-efficiency indicators were all considered. We characterize the effect of improvement measures through progressive scenarios in accordance with practical processes. Measures are suggested to effectively guide the development of a P-chemical circular economy system.